ANALISIS FAKTOR YANG MEMPENGARUHI LENGTH OF STAY PASIEN DI IGD RUMAH SAKIT PUSAT PERTAMINA - Bayu Sri Ramadhan (2023)
Length of Stay is the length of time a patient is treated in a special area of the hospital. Leingth of Stay IGD meinjeilaskan long time pasiein beirada in the IGD, ranging from peindistrasi until keiluar IGD until kei inpatient room. Factors that influence the length of stay in this study are the time of arrival of patients, how to come, triage color, type of supporting examination and type of medical decision. This research method uses a cross sectional design with a simple random sampling type with a sample size of 327 respondents. The results of statistical analysis in this study showed that there was a significant relationship between the variables of triage color, type of supporting examination and type of medical decision with length of stay with p value <0.05 and there was no significant relationship between the variables of arrival time and method of arrival with length of stay with p value> 0.05. In this study, it was found that the average length of stay of patients in the emergency room of Pertamina Central Hospital was < 4 hours.